Bloomsbury, modernism, and the reinvention of intimacy - Wolfe, Jesse, 1970- (Cambridge ; New York : Cambridge University Press, 2011)
"Bloomsbury, Modernism, and the Reinvention of Intimacy integrates studies of six members and associates of the Bloomsbury group into a rich narrative of early twentieth century culture, encompassing changes in the demographics of private and public life, and Freudian and sexological assaults on middle-class proprieties Jesse Wolfe shows how numerous modernist writers felt torn between the inherited institutions of monogamy and marriage and emerging theories of sexuality which challenged Victorian notions of maleness and femaleness. For Wolfe, this ambivalence was a primary source of the Bloomsbury writers' aesthetic strength: Virginia Woolf, D. H. Lawrence, and others brought the paradoxes of modern intimacy to thrilling life on the page. By combining literary criticism with forays into philosophy, psychoanalysis, sociology, and the avant-garde art of Vienna, this book offers a fresh account of the reciprocal relations between culture and society in that key site for literary modernism known as Bloomsbury"--
"Popular and scholarly interests in Bloomsbury have been robust in recent years, with film adaptations of Virginia Woolf's and E. M. Forster's novels, homages by Michael Cunningham and Zadie Smith, biographies of several group members, critical examinations of its literary and philosophical importance, and studies of its role in the history of liberalism, feminism, pacifism, gay liberation, and other aspects of culture and politics. This interest suggests that Bloomsbury illuminates many dimensions of modern life. The current turn in modernist studies - toward examining modernity (a social phenomenon) as the context for modernism (aesthetic responses to this phenomenon) - also suggests that Bloomsbury deserves a central role in the story of literary modernism"--
Machine generated contents note: Introduction: narrating Bloomsbury; Part I. Philosophical Backgrounds: 1. The apostle: yellowy goodness in Bloomsbury's bible; 2. The analyst: Freud's denial of innocence; Part II. Defeated Husbands: 3. The Bloomsburian: Forster's missing figures; 4. The adversary: the love that cannot be escaped; Part III. Domestic Angels: 5. The Bloomsburian: Woolf's sane woman in the attic; 6. The acolyte: a return to essences; Conclusion: the prescience of the two Bloomsburies; Appendices; Notes; Bibliography; Index.
Includes bibliographical references (pages 240-257) and index.
31298, 31299
Keywords: English fiction -- 20th century -- History and criticism; Intimacy (Psychology) in literature; Bloomsbury group; Intimacy (Psychology); Modernism (Literature) -- Great Britain; Literature and society -- Great Britain -- History -- 20th century; English literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh